Hypertension and obesity in cardiology outpatients: a cross-sectional study - Onur Dalgic; Dincer Atila; Yasemin Kilic Ozturk (SERNEV, 2019)
Introduction: Atherosclerotic cardiovascular diseases are the leading causes of deathworldwide. Both hypertension and obesity are frequent in Turkey and are seen inaround 30% of the population. This study aimed to determine the prevalence ofhypertension and to investigate its relationship with obesity in patientsadmitted to a cardiology outpatient clinic.Methods: This descriptive cross-sectional study wasconducted between the 15th of January and the 28th of February 2018 at theMedical Park İzmir Hospital Cardiology Polyclinics. Data were collected from 55out of 256 people who were referred to the clinic on the specified dates. Datawere collected about systolic and diastolic blood pressures, height, weight,gender, age category, educational status, marital status, and history ofhypertension.Results: Of the participants, 35(63.6%) were men, and 20 (36.4%) were women. The mean age and body mass indexvalues were 44.60±11.03and 28.18±3.89kg/m2, respectively. In total, 85.4% wereoverweight or obese. The mean systolic and diastolic blood pressures were140.09±7.99 mmHg and 90.69±7.07 mmHg, respectively. 31 (56.4%) patients hadsystolic, 34 (61.8%) had diastolic, and 37 (67.3%) had systolic or diastolichypertension. Of those with hypertension, 26 (70.2%) were not aware of theircondition. In the regression analysis, gender was the only independent factorpredicting high blood pressure (p=0.005; odds ratio=6.4).Conclusion: Hypertension and obesity were common amongpatients in the cardiology outpatient clinics. Family physicians are expectedto be competent in managing common health problems and are focused onpreventive health practices, and thus, they should take a more active role inthe struggle against hypertension and obesity.